ENVIRONMENTAL ACCOUNTING AS A MEANS OF DISCLOSING CORPORATE SOCIAL RESPONSIBILITY (CSR) AND ITS EFFECT ON CORPORATE IMAGE - Hermiyetti; Usmar (Adisam Publisher, 2025)
In the era of globalization and increasing environmental awareness, companies are not only expected to focus on profitability but also social responsibility and environmental preservation. Environmental accounting comes as a vital tool in supporting effective Corporate Social Responsibility (CSR) disclosure, enabling companies to measure, manage, and report their impact on the environment in a systematic and transparent way. The research method in this study uses literature study. The results show that environmental accounting facilitates companies in managing resources more efficiently, identifying opportunities to save costs, and making sustainable decisions. Effective implementation of environmental accounting can contribute to increased accountability and precision in environmental reporting, strengthen communication with stakeholders, and meet market expectations for transparency and social responsibility.